THE ROLE OF THE NATIONAL AMIL ZAKAT AGENCY OF AGAM REGENCY IN RAISING AWARENESS OF MUZAKI IN NAGARI BAYUA TO PAY AGRICULTURAL ZAKAT - Manfaluthi Manfaluthi; Zuwardi Zuwardi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
This research is motivated by the tendency of farmers not to pay agricultural zakat, as for the community factors that do not want to pay zakat, lack of knowledge, farmers feel a lack of paying agricultural zakat, lack of awareness of farmers, therefore the role of the amil zakat agency has informed and has also gathered the Nagari Bayua farmer community at the sub-district office, but only a few farmers were present. Until now, only a few farmers have paid their agricultural zakat to BAZNAS, it's just that farmers who have reached their nisab pay their agricultural zakat directly to people who are entitled to receive zakat and there are also farmers who pay zakat to relatives who are not entitled to zakat. Public awareness about the obligation to pay zakat for agricultural products (rice) in Nagari Bayua, Agam Regency is very lacking, awareness regarding the obligation to pay zakat for agricultural products, especially rice, is an indication that the community is not yet aware of the importance of paying zakat for agricultural products (rice). The majority of the work of the people of Nagari Bayua, namely farmers, sometimes has difficulty meeting their daily needs, thus the existence of the Agam district national Amil Zakat Agency so that the people of Nagari Bayua can pay Zakat from rice paddy farming to BAZNAS and distribute it by BAZNAS to asnaf 8 (fakir, poor, amil, converts, riqab, gharim, fisabilillah, ibnu sabil).